Application of Genetic Algorithm to Determine Thermal Properties of Microelectronic Layered Structures - Arsoba, Robert; Suszyński, Zbigniew (Studia Informatica. System and information technology, 2008)
In the paper, possibilities of application of genetic algorithms to determine thermal properties depth profile in microelectronic layered structures were presented. A developed com- putational method was described and results obtained using the method for a thyristor structure were presented.